Scope of Public Finance: A Review - Yamini (Innovative Research Thoughts, 2018)
The study of government revenue and expenditures is known as public finance. Finance refers to the community's monetary resources, such as its coinage and the money it earns from taxation and spending. However, data on residents of a certain area are only gathered when they are given their names in public. On the other side, it is about money coming in and going out. In this sense, public finance might be defined as the study of government revenue and expenditures.